Distribution characteristics of organic selenium in Se-enriched Lactobacillus (Lactobacillus paracasei). (1st August 2022) - Sun, Yuhan; Wang, Huanzi; Zhou, Lei; Chang, Mengjia; Yue, Tianli; Yuan, Yahong; Shi, Yiheng
Abstract: The accumulation of organic selenium (Se) by lactic acid bacteria (LAB) showed excellent biosafety and absorption efficiency. Identification of Se-enriched strains and the production of Se-enriched products by fermentation are popular research areas. However, there are few studies that focus on the distribution characteristics of Se in cells. In this study, a Se-enriched dominant Lactobacillus Paracasei 20241 was selected to characterize the distribution of Se on the cell surface and inside the cell. The results showed that L. paracei can convert sodium selenite into zero-valent Se and organic Se. The former was then released outside the cell and the latter was combined with cell components. The content of organic Se in the cells was 2144.99 ± 123.16 μg/g, accounting for 52.73% of the total Se. Compared with cellular polysaccharide and nucleic acid, protein exhibited the highest Se binding ability of 864.03 ± 26.04 μg/g, indicating that the main form of organic Se was selenoprotein. Thus, Lactobacillus Paracasei 20241 is expected to be used as a dietary supplement for Se-enrich biomass probiotics. Graphical abstract: Image 1 Highlights: Lactobacillus Paracasei 20241 with Se biotransformation was selected. Inorganic Se was bio-transformed to organic Se by Lactobacillus Paracasei 20241. The Se distribution of Lactobacillus Paracasei was confirmed. Lactobacillus Paracasei could be a good candidate as a Se-enriched food or supplement.